Optimal Polynomial Decay to Coupled Wave Equations and Its Numerical Properties - R. F. C. Lobato; S. M. S. Cordeiro; M. L. Santos; D. S. Almeida Júnior (Journal of Applied Mathematics)
In this work we consider a coupled system of two weakly dissipative wave equations. We show that the solution of this system decays polynomially and the decay rate is optimal. Computational experiments are conducted in the one-dimensional case in order to show that the energies properties are preserved. In particular, we use finite differences and also spectral methods.